1996
DOI: 10.1111/j.1399-0039.1996.tb02523.x
|View full text |Cite
|
Sign up to set email alerts
|

The human leukocyte antigen TAP2 gene defines the centromeric limit of melanoma susceptibility on chromosome 6p

Abstract: A single human leukocyte antigen (HLA) class II allele, DQB1*0301, is strongly associated with melanoma, and the HLA-DR locus provides the telomeric boundary for melanoma susceptibility in the HLA class II region of chromosome 6. However, the centromeric boundary is unknown. This study was designed to determine whether the adjacent upstream transporter associated with antigen processing (TAP) locus, TAP2, constitutes the centromeric boundary of disease susceptibility in melanoma. Molecular oligotyping of TAP2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
0
7
0
1
Order By: Relevance
“…Involvement of immune mechanisms in the aetiology and/or pathogenesis of melanoma has been suggested 1,4,9,28–31 and many studies have examined the relations between HLA class II loci and this malignancy 2–11 . However, the results of most of these studies remain controversial, with no consensus about the association of specific HLA class II alleles with susceptibility or resistance to melanoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Involvement of immune mechanisms in the aetiology and/or pathogenesis of melanoma has been suggested 1,4,9,28–31 and many studies have examined the relations between HLA class II loci and this malignancy 2–11 . However, the results of most of these studies remain controversial, with no consensus about the association of specific HLA class II alleles with susceptibility or resistance to melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…However, homozygosity for the HLA-DQA1 locus (and, perhaps, for the HLA-DQB1*0301 allele) might be considered a potential risk factor for developing melanoma depending on the person's genetic background and, perhaps, on certain environmental conditions. Over the last three decades, several studies have examined the involvement of the HLA system in the aetiology of malignant melanoma, [1][2][3][4][5][6][7][8][9][10][11] and it has been speculated that HLA class II association might be the immunogenetic basis for melanoma susceptibility. 1 However, reports have not shown consistent results perhaps because of sample size, patient series heterogeneity, the choice of control populations and differences in the techniques employed for the detection of HLA antigens or alleles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…91 The association between human leukocyte antigen (HLA) class II loci and CMM is a topic of widespread debate as it has been postulated that this relationship might be the immunogenetic basis for melanoma susceptibility. 94,95 In an early study of 45 Caucasian patients with CMM, Lee et al reported that 56% carried the HLA class II allele, DQB1*0301, versus only 27% of Caucasian controls (P = .003); additionally, the allele was associated with advanced disease at diagnosis, with 44% of the DQB1*0301-positive patients presenting with metastases compared with only 5% of DQB1*0301-negative patients (P = 0.003) (see Table II). 96 Another study by these same authors found that stage I or II CMM patients who carried the HLA-DQB1*0301 allele were at an increased risk of developing recurrent disease compared with stage-matched patients who were DQB1*0301-negative (see Table II).…”
Section: Immune-related Genesmentioning
confidence: 98%
“…The relationship between HLA class II alleles and susceptibility to melanoma is still considered controversial, since some investi-gators have found DR4 and DR5 class II antigens to be associated with melanoma (4, 5), whereas others did not confirm these data (6,7). Recently, however, Lee et al (8,9) have found a significant association of HLA DQB1*0301 allele with increased risk of melanoma.…”
Section: If Melanoma Cells Express Hla Class II Antigens and Thus Funmentioning
confidence: 99%